Circulating levels of butyrate are inversely related to portal hypertension, endotoxemia, and systemic inflammation in patients with cirrhosis. Issue 10 (25th July 2019) - Juanola, Oriol; Ferrusquía-Acosta, José; García-Villalba, Rocío; Zapater, Pedro; Magaz, Marta; Marín, Alicia; Olivas, Pol; Baiges, Anna; Bellot, Pablo; Turon, Fanny; Hernández-Gea, Virginia; González-Navajas, José M.; et al.
ABSTRACT: Short‐chain fatty acids (SCFAs) are gut microbiota‐derived products that participate in maintaining the gut barrier integrity and host's immune response. We hypothesize that reduced SCFA levels are associated with systemic inflammation, endotoxemia, and more severe hemodynamic alterations in cirrhosis. Patients with cirrhosis referred for a hepatic venous pressure gradient (HVPG) measurement ( n = 62) or a transjugular intrahepatic portosystemic shunt placement ( n = 12) were included. SCFAs were measured in portal (when available), hepatic, and peripheral blood samples by GC‐MS. Serum endotoxins, proinflammatory cytokines, and NO levels were quantified. SCFA levels were significantly higher in portal vs . hepatic and peripheral blood. There were inverse relationships between SCFAs and the severity of disease. SCFAs (mainly butyric acid) inversely correlated with the model for end‐stage liver disease score and were further reduced in patients with history of ascites, hepatic encephalopathy, and spontaneous bacterial peritonitis. There was an inverse relationship between butyric acid and HVPG values. SCFAs were directly related with systemic vascular resistance and inversely with cardiac index. Butyric acid inversely correlated with inflammatory markers and serum endotoxin. A global reduction in the blood levels of SCFA in patients with cirrhosis is associated with a more advanced liver disease, suggesting its contribution to disease progression.—Juanola, O., Ferrusquía‐Acosta, J., García‐Villalba, R., Zapater, P., Magaz, M., Marín, A., Olivas, P., Baiges, A., Bellot, P., Turon, F., Hernández‐Gea, V., González‐Navajas, J. M., Tomás‐Barberán, F. A., García‐Pagán, J. C., Francés, R. Circulating levels of butyrate are inversely related to portal hypertension, endotoxemia, and systemic inflammation in patients with cirrhosis. FASEB J. 33, 11595–11605 (2019). www.fasebj.org